Role of erythropoietin and its receptor in the development of endometriosis in rats - Günal, Mehmet Yalçın; Ozansoy, Mehmet; Kılıç, Ülkan; Keskin, İlknur; Özdemir, Ekrem Musa; Aslan, İsmail; Eren, Zehra; Ersavaş, Cenk; Kılıç, Ertuğrul (Galenos Yayıncılık, 2019)
Objective: Besides its hematopoietic function, erythropoietin (EPO) may protect tissues from degenerative disorders. As such, EPO and its receptors were revealed in nonhematopoietic cells, including stromal and endometrial epithelial cells. However, the role of EPO in endometrial disorders is still unknown. Here, we aimed to examine the role of EPO and its receptor activation in the development of endometriosis in rats. Material and Methods: Animals were treated with EPO, darbepoietin (the synthetic form of EPO) or EPO's receptor activator, methoxy polyethylene glycol-epoetin beta (MIRCERA), after development of endometriosis. Endometriosis was induced by estrogen-administration following surgical attachment of endometrial surface on the inner abdominal wall. Treatments were started 3 weeks after induction of endometriosis and continued for the following 3 weeks. For the analysis of recurrence of endometriosis, additional analyses were conducted 3 weeks after cessation of treatments. Results: As compared with vehicle-treated animals, lesion size was reduced significantly and recurrence of endometriosis was not observed in all treatment groups. Histopathologic examination revealed that EPO and darbepoietin were more effective than MIRCERA- and vehicle-treated animals. Conclusion: Here we provide evidence that EPO is a promising candidate for the treatment of endometriosis. Our histopathologic results in particular indicate that EPO is more effective than its receptor activator MIRCERA in the development endometriosis.
WOS: 000459590500009
PubMed ID: 29916217
Keywords: Endometriosis; Darbepoietin; Erythropoietin; MIRCERA; Receptor Activator